1975
DOI: 10.1073/pnas.72.11.4674
|View full text |Cite
|
Sign up to set email alerts
|

Aging and its relation to cell growth and differentiation in Drosophila imaginal discs: developmental response to growth restricting conditions.

Abstract: The development of Drosophila organ discs can be arrested by culturing them in adult male flies. These aged discs lose some of their differentiation competence and form incomplete imaginal structures. The more advanced the aging, the greater the loss of competence. Discs made to differentiate prematurely show deficiencies similar to aged discs. The age-induced defects can be repaired in a larval milieu. Special hormonal conditions, but not cell multiplication, are apparently involved in the recovery process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Toward testing these hypotheses, Schweizer and Bodenstein (1975) endocrinologically confirmed that fully grown (proliferated) genital discs taken from larvae 4 h prior to pupariation, upon transplantation into back into a mature (same age) larval host, would then proceed to differentiate during the subsequent host pupariation through adult eclosion. If, instead, the fully proliferated disc was first cultured in an adult male host, the disc lost its competence to differentiate when then transplanted into mature 3rd instar larva.…”
Section: Expression Of Developmental Program By Imaginal Discsmentioning
confidence: 89%
“…Toward testing these hypotheses, Schweizer and Bodenstein (1975) endocrinologically confirmed that fully grown (proliferated) genital discs taken from larvae 4 h prior to pupariation, upon transplantation into back into a mature (same age) larval host, would then proceed to differentiate during the subsequent host pupariation through adult eclosion. If, instead, the fully proliferated disc was first cultured in an adult male host, the disc lost its competence to differentiate when then transplanted into mature 3rd instar larva.…”
Section: Expression Of Developmental Program By Imaginal Discsmentioning
confidence: 89%
“…One reason may be that the cells at the dorsal cut rarely contribute to the regenerate (Abbott et al, 1981), indicating that they are not participating in the proliferating blastema. The induction of proliferation however is a prerequisite for regeneration and TD (Schubiger, 1973; Schweizer and Bodenstein, 1975). In addition WG and Dpp must interact for TD to occur (Maves and Schubiger, 1998), but at the dorsal cut wg is not expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal analyses reveal that imaginal disc regeneration proceeds from blastema cells [28,31] and that transdetermined structures derive from, and are clonally related to, the newly regenerated tissue [23][24][25]. Transdetermination requires cell division because when disc fragments are cultured in conditions in which cell division is inhibited, no transdetermination is observed [33,34]. Vertebrate limb regeneration also proceeds through the formation of a blastema, in which cells undergo dedifferentiation and proliferation (reviewed in [1,2]).…”
Section: Transdetermination Is Strongly Associated With Regeneration mentioning
confidence: 99%